SISTEM INFORMASI GEOGRAFIS PEMETAAN POTENSI LIKUEFAKSI DI PROVINSI GORONTALO - Paputungan, Febrianti; Abdillah, Tajjudin; Ahaliki, Budiyanto; H. Dai, Roviana (Universitas Muhammadiyah Sorong, 2025)
This research discusses the development of a Geographic Information System (GIS) using a prototype-based method for mapping liquefaction potential in Gorontalo Province. Liquefaction is a geological phenomenon that occurs when soil loses its strength due to earthquake tremors, potentially causing severe damage to infrastructure and buildings. The main objective of this study is to provide spatial information related to areas at risk of liquefaction by utilizing web-based GIS technology. The system was designed through the stages of the prototype method, starting from communication, data collection, rapid design, initial prototype development, to evaluation and refinement based on user feedback. The research focused on Gorontal City, covering 48 villages, where disaster parameters such as wave, vibration, ground cracks, land subsidence, landslides, and liquefaction were the main concerns. The system evaluation was conducted using the System Usability Scale (SUS) method on 10 respondents, consisting of practitioners in the fields of geophysics and disaster management. The test results showed an average score of 73, which was categorized as Acceptable with a grade of C, and the user satisfaction level was in the Good category based on the adjective rating scale. The majority of users stated that the system was easy to understand, the interface navigation was intuitive, and the interactive map visualization feature was very helpful in the analysis process. Overall, the results of this study indicated that the developed system was not only capable of visualizing liquefaction potential spatially but also had a good level of acceptance and usability among users. This system was considered effective and suitable for use as a tool in disaster mitigation planning, spatial management, and risk-based decision-making for land disasters in Gorontalo Province.